The Vulnerability-Stress-Model—Holding Up the Construct of the Faulty Individual in the Light of Challenges to the Medical Model of Mental Distress - Demke, Elena (Frontiers in Sociology, 2022)
In the 1970s, the course seemed to be set for a reconciliation of the controversy around the somatic versus the social nature of mental distress. The biopsychosocial model (Engel 1977) and the vulnerability-stress-model (Zubin & Spring 1977) were influential agents in this move, but a medicalized somatic view on mental distress persisted nonetheless (Read et. al. 2009). The reasons for this persistence are complex, and include questions of structural power. However, the adherence to a fundamental framing of a problem may persist not only out of conviction, but also unwittingly. The vulnerability-stress-model (Zubin & Spring 1977) allowed recipients to effectively stick to the implications of a medicalized view of the faulty individual who falls ill, while also allowing them to believe they integrated the social dimensions of the problem. A close reading and hermeneutical interpretation of the text by Zubin and Spring (1977) and an analysis of its use in psychoeducation serve as a case study in this respect. The vulnerability-stress-model (simply called “vulnerability model” by Zubin and Spring; more often “stress-vulnerability model” by English speaking recipients, and “vulnerability-stress-model” by German authors) was a success story: since its publication by Zubin and Spring in 1977, it has been the point of reference for numerous scholarly and “psychoeducational” adaptations. It was soon extended from the diagnosis of schizophrenia to various psychiatric diagnoses, understanding mental distress as the result of a trait/state-interaction in the shape of „deviant coping patterns“ (Zubin & Spring, p. 112). Recipients appraised the integration of environmental and dispositional factors, some of them opposing the supposed originally integrative intention of the VSM to reduced applications of it (Schmidt 2012). However, it can be argued that this integration is a matter of rhetorics rather than argumentative essence. Their argument, depending on the use of metaphors, and their referencing, amount to a confirmation of a medicalized view on mental distress and a downplaying of the role played by societal factors. Applied to psychoeducation, this paradoxical combination reinforces a view of the persons in question as individually vulnerable, rather than socially wounded and thus contributes to turning individual difference into disability.